2005
DOI: 10.1159/000082011
|View full text |Cite
|
Sign up to set email alerts
|

Access Monitoring Does Not Really Improve Outcomes

Abstract: It is widely accepted that hemodialysis access monitoring combined with preemptive percutaneous transluminal angioplasty (PTA) improves outcomes. The many studies that have evaluated monitoring during the last decade provide an opportunity to examine whether this hypothesis is valid. Because synthetic grafts are more likely than autogenous arteriovenous fistulas to benefit from monitoring, this review is restricted to grafts. Recent studies show that monitoring does not accurately predict graft thrombosis or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In our patients, 44% of thromboses occur without a preceding reduction in Q (10,11). Consequently, the efficacy of flow surveillance has been debated at several recent nephrology symposia and in the literature (12)(13)(14).…”
mentioning
confidence: 79%
“…In our patients, 44% of thromboses occur without a preceding reduction in Q (10,11). Consequently, the efficacy of flow surveillance has been debated at several recent nephrology symposia and in the literature (12)(13)(14).…”
mentioning
confidence: 79%
“…Preemptive intervention (either radiological or surgical) extends the duration of access sites and may even reduce health care costs, [1][2][3][4][5] although, because of recent negative trials, this issue has become more controversial. 6 The Kidney Disease Outcome Quality Initiative (K/DOQI) Clinical Practice Guidelines for Vascular Access strongly recommend surveillance of vascular access monitoring by periodical flow measurements. 7 The most commonly used technique to measure access flow is the saline dilution technique, as introduced by Krivitski.…”
mentioning
confidence: 99%
“…Some papers [12,13] have criticized the monitoring of vascular access flow as unnecessary because it has not been shown to prolong access patency. It has even been suggested that, on the contrary, it might even lead to an increase in the re-stenosis incidence due to vascular access endothelium injury during forced dilation using balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%